Contraction-Induced Changes in Hydrogen Bonding of Muscle Hydration Water - Yoo, Hyok (American Chemical Society, 2014)
[Image: see text] Protein–water interaction plays a crucial role in protein dynamics and hence function. To study the chemical environment of water and proteins with high spatial resolution, synchrotron radiation-Fourier transform infrared (SR-FTIR) spectromicroscopy was used to probe skeletal muscle myofibrils. Observing the OH stretch band showed that water inside of relaxed myofibrils is extensively hydrogen-bonded with little or no free OH. In higher-resolution measurements obtained with single isolated myofibrils, the water absorption peaks were relatively higher within the center region of the sarcomere compared to those in the I-band region, implying higher hydration capacity of thick filaments compared to the thin filaments. When specimens were activated, changes in the OH stretch band showed significant dehydrogen bonding of muscle water; this was indicated by increased absorption at ∼3480 cm(–1) compared to relaxed myofibrils. These contraction-induced changes in water were accompanied by splitting of the amide I (C=O) peak, implying that muscle proteins transition from α-helix to β-sheet-rich structures. Hence, muscle contraction can be characterized by a loss of order in the muscle–protein complex, accompanied by a destructuring of hydration water. The findings shed fresh light on the molecular mechanism of muscle contraction and motor protein dynamics.